Leveraging the spotlight of leadership what every leader should know - Conger, Jay Alden ([Stanford, CA] : Mill Valley, CA : Stanford Video ; [Distributed by] Kantola Productions, 2008)
Managers and executives sit in a natural spotlight because of their leadership role. The best leaders harness the spotlight as a powerful tool to get things done; influencing the behavior and decision-making of their staff, even when they are not present
Taped live March 12, 2008 at Stanford University
Jay Conger, Professor of Leadership, Claremont McKenna College.
DVD.
Keywords: Leadership